2022
DOI: 10.2337/db22-0233
|View full text |Cite
|
Sign up to set email alerts
|

Smooth Muscle Insulin Receptor Deletion Causes Voiding Dysfunction: A Mechanism for Diabetic Bladder Dysfunction

Abstract: Diabetic bladder dysfunction (DBD) is the most common complication in diabetes mellitus (DM). Myogenic abnormalities are common in DBD, however, the underlying mechanisms leading to these remains unclear. To understand the importance of smooth muscle insulin receptor (IR)-mediated signaling in the pathogenesis of DBD, we conditionally deleted it to achieve either heterozygous (SMIR+/−) or homozygous (SMIR−/−) deletion in smooth muscle cells. Despite impaired glucose and insulin tolerance seen with SMIR−/− mice… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Based on the above findings, the use of sustained-release low-dose insulin injections can create a relatively stable model of DM-induced LUTD. Moreover, low-dose insulin demonstrates a certain protective effect against lower urinary tract dysfunction, potentially mediated through its interaction with insulin receptors in the lower urinary tract 20 . However, it is important to note that low-dose insulin cannot fully reverse the damage caused by diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the above findings, the use of sustained-release low-dose insulin injections can create a relatively stable model of DM-induced LUTD. Moreover, low-dose insulin demonstrates a certain protective effect against lower urinary tract dysfunction, potentially mediated through its interaction with insulin receptors in the lower urinary tract 20 . However, it is important to note that low-dose insulin cannot fully reverse the damage caused by diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…As the most common complication of DM, DBD presents many symptoms such as overactive bladder, bladder emptying disorder and urinary retention, which seriously affects patients' quality of life [13]. In the study, the mechanism of Nrf2 in the pathogenesis of DBD is further explored by establishing T2DM mice model and Nrf2 gene knockout mouse with T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…When methylglyoxal—a reactive by-product of glycolysis found at high levels in diabetic plasma—was administered to healthy mice for four weeks, an overactive bladder phenotype was observed in the complete absence of hyperglycemia [ 51 ]. Furthermore, an intriguing recent study from Chen et al [ 52 ] proposed a novel theory on the etiology of DVD. Using a smooth muscle-specific insulin receptor knockout mouse, they showed that voiding phenotypes resembling DVD could be induced despite the mutation having no effect on blood glucose levels.…”
Section: Discussionmentioning
confidence: 99%